Introducing Criticizing of Orientalism from Within - Mohamed Ali, Halimah (LingPoet: Journal of Linguistics and Literary Research, 2025)
This paper outlines the theoretical framework Criticising Orientalism From Within (C.O.F.W.) that foregrounds the methodology of research for the thesis Orientalism From Within: A Critical Study Of Pandering And Catering To The West In Three Contemporary Indian-English Novels (2006) Universiti Kebangsaan Malaysia and the book Orientalism from Within Arundhati Roy and Her Contemporaries (2010) Penerbit Universiti Sains Malaysia.The workings of imperialism and neo-colonialism in the contemporary situation is pitted against postcolonialism via Indian-English literature, and explored in the chapter titled Criticising Orientalism From Within specifically and the study generally. This chapter is an eclectic fusion of six modern theorists. The slant or methodology used is criticism and analysis of the three novels vis-à-vis an eclectic or diverse theoretical framework. However, this paper concentrates on Dipankar Gupta’s book India is for Sale and his term Orientalism from Within that this research has borrowed, adapted and adopted as a title to the theoretical framework, the thesis, and the book mentioned above. All the other theorists employed to create the theoretical framework will be discussed generally.